Analysis of Technical Efficiency of Paddy and Maize Farming - Surojudin Sodiq; Tri Haryanto (Gorontalo Development Review, 2021)
This study aims to determine the level of technical efficiency of paddy and maize farming in Gorontalo Province in 2019. The data used comes from the 2019 Ubinan Survey conducted by BPS Gorontalo Province. The total samples studied were 833 farming units, consisting of 392 paddy farming units and 441 maize farming units. The analysis method used is Data Envelopment Analysis (DEA). The results showed that most of the paddy and maize farming in Gorontalo Province in 2019 had not yet reached the full level of technical efficiency. The average level of technical efficiency in paddy farming was 68.7 percent, while the average level of efficiency in maize farming was only 56.7 percent.